Development of autogrease electric motor’s bearing system - Ahmad Fatihy, Mohd Subbri (2012)
Even with an advancement of technologies, most of industries are still using manual greasing method in maintaining the electric motor’s performance. Even though it has helped to maintain the motors performance, yet it presents associated problems such that difficulties in maintaining the regreasing time interval and regreasing volume as well as reaching motor in an inaccess area. These motivating factors lead this project to develop automatic grease system in order to extend bearing lifetime without danger the maintenance technician; it also will increase electric motor performance. This project focuses on developing a system that capable to automate greasing an electrical motor according to required specification or preventive and maintenance plan.